Thymic T-Cell Production Is Associated With Changes in the Gut Microbiota in Young Chicks - Cheng, Jiaheng; Yuan, Yushan; Zhao, Fang; Chen, Jianwei; Chen, Peng; Li, Ying; Yan, Xia; Luo, Chenglong; Shu, Dingming; Qu, Hao; Ji, Jian (Frontiers in Immunology, 2021)
Increasing studies show that gut microbiota play a central role in immunity, although the impact of the microbiota on mediation of thymic T cells throughout life is not well understood. Chickens have been shown to be a valuable model for studying basic immunology. Here, we show that changes in the gut microbiota are associated with the development of thymic T cells in young chickens. Our results showed that T-cell numbers in newborn chicks sharply increased from day 0 and peaked at day 49. Interestingly, the α-diversity score pattern of change in gut microbiota also increased after day 0 and continued to increase until day 49. We found that early antibiotic treatment resulted in a dramatic reduction in gut alpha diversity: principal component analysis (PCA) showed that antibiotic treatment resulted in a different cluster from the controls on days 9 and 49. In the antibiotic-treated chickens, we identified eight significantly different (p < 0.05) microbes at the phylum level and 14 significantly different (p < 0.05) microbes at the genus level, compared with the controls. Importantly, we found that antibiotic treatment led to a decreased percentage and number of T cells in the thymus when measured at days 9 and 49, as evaluated by flow cytometry. Collectively, our data suggest that intestinal microbiota may be involved in the regulation of T cells in birds, presenting the possibility that interventions that actively modify the gut microbiota in early life may accelerate the maturation of humoral immunity, with resulting anti-inflammatory effects against different pathogens.